The relationship between safety management practices and safety behaviours among employees of International Islamic University Malaysia - Rosli, Hassan (2018)
Occupational safety is an issue of considerable importance in any organization. The management needs to ensure that the work environment is safe for the employees. However, occupational safety is not only the responsibility of the management but the whole organization including the employees. Literature on occupational safety shows that employees' safety behaviour has direct or indirect link to safety at the workplace. Unsafe behaviours of employees can contribute to workplace accidents. For a better understanding of occupational safety in an academic setting, this study surveyed 329 employees of International Islamic University Malaysia to find out the level of safety management practices, the level of safety behaviours of the employees and whether or not there is a relationship between safety management practices and safety behaviours. The questionnaire used for this study was adapted from a number of previous studies. The study found that the university's employees perceived safety management practices and their safety behaviours at a satisfactory level. Correlation analyses show that there is a positive relationship between safety management practices and safety behaviours. These findings point to the importance of providing reliable safety management practices in instilling good safety behaviours. These findings indicate that reliable safety management practices are important in improving a safe working culture among the employees.